APPLICATION OF MULTIFACTORIAL EXPERIMENTAL DESIGN FOR OPTIMIZATION OF PRODIGIOSIN PRODUCTION USING SERRATIA MARCESCENS MBB01, MBB02 AND MBB05 - BV, PRADEEP; P, AKILANDESWARI; V, USHA RANI; M, PALANISWAMY (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was aimed at investigating the prodigiosin production under optimized conditions with different parameters such as temperature, incubation time, substrate concentration, and inoculum size. Methods: Response surface methodology was found to be useful in optimizing and determining interactions among process variables in prodigiosin production by applying Box–Behnken and face-centered central composite design. Results: Prodigiosin producing Serratia marcescens (SM) MBB01, MBB02, and MBB05 were isolated from soil (Western Ghats Ecosystem). The significant R value was 0.9666, 0.9459, and 0.9433, and the maximum experimental response for prodigiosin production was 497, 690, and 560 mg/mL, whereas the predicted value was 495.3, 706.6, and 574.8 mg/mL for SM MBB01, SM MBB02, and SM MBB05, respectively. 2 Conclusion: Statistically optimized conditions by Box–Behnken design found to be very significant in improved pigment production by SM MBB01, MBB02, and MBB05. The correlation between the predicted and observed values indicates the adequacy of the model. Keywords: Prodigiosin, Serratia marcescens, RSM.